MEMBANGUN BUDAYA ORGANISASI LEMBAGA PENDIDIKAN: PROSES MEMBANGUN NILAI DALAM BUDAYA ORGANISASI UNTUK PENGEMBANGAN LEMBAGA PENDIDIKAN - Chusnul Chotimah (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Culture is dynamic rather than rigid and static. Culture is the implementation of state of mind and normative values of the society. The culture of organization at schools is socialized through internalization of common beliefs and values such as trust, behaviors or attitudes and symbols upon which the norms of collective behaviors are based. Successful internalization of those common values and norms will create secure and conducive working environments among the members, which eventually enhance their organizational commitments and loyalties. In other words, a strong organizational culture will provide the required structures and controls without heavily relying on formal bureaucracies which in many cases can discourage motivation and innovation.Keywords: Budaya Organisasi, Nilai